Building maintenance practices: analysis on user satisfaction of physical facilities at old railway station building / Nur Asyikin Salleh and Nur Fadhilah Bahardin - Salleh, Nur Asyikin; Bahardin, Nur Fadhilah (2023)
Historical building preservation is critical for protecting cultural heritage and providing an unequivocal user experience. This research focuses on examining user satisfaction with building maintenance practices at the old railway station building, a prominent heritage site with a rich architectural and historical background. The effectiveness of the maintenance procedures in the preservation and upkeep of the historic railway station structure lends to the degree of satisfaction of its users. A thorough review of pertinent literature was performed to comprehend the theoretical foundations of building maintenance practices, historic preservation, and user satisfaction. It also looks into how user perception, expectations, and preferences affect the extent of the maintenance practices. The findings provide useful direction for those involved in the preservation and upkeep of historic railway station buildings, empowering them to make wise choices that will increase user satisfaction and maintain the long-term viability of these architectural gems.